Sustainable management of simulated coffee processing wastewater using micro-aeration enhanced anaerobic digestion: a long-term technical evaluation - Taiwo, Kayode J.; Ogundipe, Samuel O.; Kerr, William L.; Pegg, Ronald B.; Suh, Joon Hyuk; Usack, Joseph G. (Frontiers in Sustainability, 2025)
IntroductionCoffee bean production generates high volumes of contaminated processing water in regions of the world that often lack the necessary infrastructure to provide adequate treatment. This coffee processing water (CPW) contains high organic loads alongside ecopharmokinetic and recalcitrant compounds, such as caffeine and tannins, which, when discharged, pollute the environment and degrade freshwater supplies that nearby populations may depend on.MethodsIn this study, an anaerobic digestion (AD) reactor and a micro-aeration enhanced anaerobic digestion (MA-AD) reactor were operated in parallel for 430 days to compare their effectiveness in treating and valorizing simulated CPW to promote a more sustainable approach to coffee production. In coffee-producing regions where access to centralized wastewater treatment facilities is limited, MA-AD offers a technologically and economically accessible option that can be implemented by industrial-scale coffee processors as well as small- to medium-scale processors in rural settings with limited technical infrastructure. To test this, oxygen was intermittently dosed into an AD microbiome, allowing for a comparative assessment across anaerobic and micro-aerobic redox regimes.ResultsThe conventional AD and MA-AD achieved comparable reductions in total and volatile solids (>48 and >60%, respectively) and total and soluble chemical oxygen demand (>66 and >86%, respectively), MA-AD exhibited significantly higher total suspended solids concentrations and turbidity in later phases, likely due to gas sparging-induced floc disruption and particulate release. pH profiles indicated a shift towards increased acidification under MA-AD, without compromising process stability, with both reactors stabilizing between pH 6.8 and 7.1. Caffeine degradation was accelerated under MA-AD at the lowest O₂ dosing level (28.73 ± 1.10 mL O₂·d−1·Lreactor−1) after spiking caffeine (>85% removal in 28 h), and decreased at higher O₂ dosing levels (100.73 ± 6.90 mL O₂·d−1·Lreactor−1; 228.60 ± 3.92 mL O₂·d−1·Lreactor−1). Finally, methane production was consistently lower in MA-AD, attributed to the oxygen sensitivity of methanogens and possible substrate competition.ConclusionThese results underscore the importance of oxygen dose regulation, redox control, and microbial adaptation in optimizing MA-AD performance. The findings support MA-AD as a promising strategy for ensuring a safer and more sustainable water supply by enhancing the treatment of ecopharmokinetic and recalcitrant compounds in CPW.